Gender Differences in Factors Associated with Delirium Severity in Older Adults with Dementia - Kolanowski, Ann M. (2014)
The purpose of this descriptive correlational study was to explore potential gender differences in the relationship of dementia severity, age, APOE status, cognitive reserve and co-morbidity, (two potentially modifiable factors), to delirium severity in older adults. Baseline data from an ongoing clinical trial and a Poisson regression procedure were used in the analyses. Participants were 148 elderly individuals with dementia and delirium admitted to post-acute care. In women, delirium severity was related to dementia severity (p= 0.002) and co-morbidity moderated that effect (p=0.03). In men, education was marginally associated with delirium severity (p=0.06). Implications for research are discussed.